PROBLEM STRUCTURE OF IMPLEMENTATION SUITABILITY OF SPACE UTILIZATION ACTIVITIES (KKPR) - Haznan, Luthfiah
After the issuance of Law No. 11 of 2020 concerning Job Creation to simplify the basic requirements for business licensing, spatial use permits (Principle Permit, Location Permit, and Land Utilization Permit (IPPT)) no longer exist. It has changed to Suitability of Space Utilization Activities (KKPR). KKPR is the conformity document between the spatial utilization activity plan and the Spatial Plan(RTR). However, in practice, various obstacles indicate that the KKPR is not yet effective and contains various complex problems. Until now, there has been no attempt to comprehensively map the problems of KKPR implementation to address KKPR implementation problems. This study aims to structure the problem of KKPR implementation as a basis for formulating recommendations for improving the KKPR system. This research is explorative with structuring the problem through four interrelated phases/stages: problem sensing, problem search, problem delineation, and problem specification, where each will produce a problem situation, meta-problem, substantive problem, and formal problem. The study results show that problems with the implementation of the KKPR can be grouped into three typologies: issues related to the KKPR implementation system, the Online Single Submission (OSS) system, and issues related to the community. Issues related to the KKPR system include regulation, coordination, automatic KKPR for the regions, technical instructions, and follow-up mechanisms. Issues related to the OSS system include errors in the OSS system and the verification of data correctness. Meanwhile, issues regarding the community include understanding business actors and socialization. The three typologies of these problems lead to accumulative impacts, namely various cases of non-compliance in implementing the KKPR in the field. As a follow-up, the government needs to strengthen procedures and regulations on KKPR applications, improve the accuracy of the OSS system, provide information that is easily accessible and easily understood by people who expect to apply for KKPR, and carry out comprehensive and equitable outreach.